Transforming command : the pursuit of mission command in the U.S., British, and Israeli armies - Shamir, Eitan, 1964- (Stanford Security Studies, 2011)
On today's complex, fragmented, fast-moving battlefield, where combatants adapt constantly to exploit one-another's weaknesses, there is a demonstrable requirement for military commanders to devolve a high level of autonomy of decision-making and action to leaders on the ground. An effective model for doing this has existed for some time in the form of mission command and has been utilized by the U.S., Israeli, and British Armies--but with mixed success. This book examines in depth the experiences of the armed forces of each of these countries in implementing mission command, and reveals the key.